The effectiveness of Interferon-Ophthalmo, an antiviral and immunotropic drug, in the treatment of adenoviral ophthalmic infections - E. V. Yani; V. V. Pozdnyakova; K. E. Seliverstova (Российский офтальмологический журнал, 2023)
Adenoviral conjunctivitis (AVC) is treated with pathogenetically determined immunotropic drugs, the most commonly used of which are combined eye drops that include recombinant human interferon alpha-2b and diphenhydramine hydrochloride. In 2020, Russia registered the first domestic generic of the original, called Interferon-Ophthalmo eye drops. Purpose: to compare the effectiveness and safety of InterferonOphthalmo and the original interferon alpha-2b + diphenhydramine drug (Ophthalmoferon) in AVC patients. Material and methods. The study included 30 patients (60 eyes) aged 18–75 years with a clinically confirmed AVC, divided into the main group and the control group, each having 15 patients. The main group received Interferon-Ophthalmo, while the control group received Ophthamoferon. The treatment procedures were identical, with the follow-up period of 15 days. Clinical manifestations of AVC were assessed according to multiple parameters: complaints of eyelid edema, eye redness, lacrimation, itching, foreign body sensation, severity of conjunctival edema and hyperemia, follicular reaction in the lower conjunctival fornix, and hemorrhages. Results. The comparative assessment of the proportion of cases of clinical recovery, performed on the 7th and the 15th days of AVC therapy, confirms the same effectiveness of the two drugs. Conclusion. Interferon-Ophthalmo has a high clinical efficacy comparable with that of the original drug Interferon alpha-2b + Diphenhydramine and can be recommended for the treatment of patients with adenoviral ophthalmic infections.